(untitled) (مجلة المنصور, 2022)
Image filtering is one of the fundamental problems in the field of image processing and computer vision. Filtering an image improves the details and consequently the usability of an image. In this paper the algorithm of hybrid median filter is presented and then software is implemented using Matlab package. The features of the implemented hybrid median filter are compared with normal median filter under different conditions and circumstances and from testing results many points are concluded